A comparative analysis of textile schools by journal publications listed in Web of ScienceTM. Issue 9 (19th August 2021) - Li, Ziqi; Poon, Hosana; Chen, Wei; Fan, Jintu
Abstract: In this study, a comparative analysis of textile schools around the world based on research journal publications is made using the most popular bibliometric evaluation methodology. The study benchmarks bibliometric evaluation of professional research institutions related to textile, apparel, fashion and clothing in recent years from 2014 to 2019. Based on Web of Science TM, a total of 124, 362 research publications (not counting conference papers) from 2014 to 2019 were found to be textile or fiber related. Out of more 1000 textile schools worldwide, 31 schools from 18 countries or territories were identified to be among the top 100 institutions contributing the textile or fiber related publications listed in Web of Science TM . These 31 textile schools are ranked in terms of productivity and citation impact, including total number of publications, publication per staff, h -index, total citations, average citations, and citation per staff. While these bibliometric measures provide some insights of the trends of the research activities and influences of textile schools in the world, they should be interpreted with caution as the quality of research contributions in terms of originality, scientific rigor and societal impact may not be reflected by the publication counts and the cites they receive.